2017
DOI: 10.1038/ijos.2016.58
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of potential inhibitors targeting Streptococcus mutans sortase A

Abstract: Dental caries is one of the most common chronic diseases and is caused by acid fermentation of bacteria adhered to the teeth. Streptococcus mutans (S. mutans) utilizes sortase A (SrtA) to anchor surface proteins to the cell wall and forms a biofilm to facilitate its adhesion to the tooth surface. Some plant natural products, especially several flavonoids, are effective inhibitors of SrtA. However, given the limited number of inhibitors and the development of drug resistance, the discovery of new inhibitors is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 41 publications
0
33
0
2
Order By: Relevance
“…The similarities between S. aureus sortase A and S. mutans sortase A also encouraged Luo et al to screen two pharmaceutical small molecule/natural product libraries in silico for sortase A inhibition. 71 The most promising compounds featured benzofurans, thiadiazoles, and pyrroles that contributed to the hydrogen bond network that most likely engages with the cysteine active site of sortase A, shutting down enzymatic activity. Two compounds with the highest possibility for development are ZINC08383458 (9) and ZININC08383439 (10).…”
Section: Sucrose-independent Anti-adhesion: Non-glucosyltransferase Mmentioning
confidence: 99%
“…The similarities between S. aureus sortase A and S. mutans sortase A also encouraged Luo et al to screen two pharmaceutical small molecule/natural product libraries in silico for sortase A inhibition. 71 The most promising compounds featured benzofurans, thiadiazoles, and pyrroles that contributed to the hydrogen bond network that most likely engages with the cysteine active site of sortase A, shutting down enzymatic activity. Two compounds with the highest possibility for development are ZINC08383458 (9) and ZININC08383439 (10).…”
Section: Sucrose-independent Anti-adhesion: Non-glucosyltransferase Mmentioning
confidence: 99%
“…Alto and co-workers used some bioinformatics approaches to design potent and selective anchoring peptide antagonist of protein kinase A [32]. Luo and co-workers used in silico screening methods such as molecular docking to analyze potential inhibitors of Sortase enzyme A of streptococcus mutans [33]. Here we arranged a new construct of InaV/N-dfpase that theoretically is suited for the expression of DFPase on the cell surface of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This study was carried out avoiding the sucrose-independent adhesion way, which has been aimed mainly at blocking sortase A, a transpeptidase involved at the anchoring of cell surface proteins, including Ag I/II, through the LPXTG motif. It has been found that several molecules can reduce biofilm formation, through the inhibition of the sortase A [39,40], such is the case of the natural phenol curcumin, (Curcuma longa) with which it has been reported inhibition S. mutans sortase A activity with IC50: 10 µM and a MIC of 175 µM [41]. However, despite the multiple benefits of this molecule,…”
Section: Adhesion Assaysmentioning
confidence: 99%
“…some toxic effects have also been evidenced related to the high doses as result from its use as a supplement in the diet [40,41]. Another natural product is named Morin, it has an inhibitory effect against S. mutans SrtA with IC50: 27.2 µM [42,43].…”
Section: Cmentioning
confidence: 99%